Neuronal Plasticity in the Amygdala Following Predator Stress Exposure - Mitra, Rupshi (Frontiers in Behavioral Neuroscience, 2019)
Predation causes robust long-term stress-related effects on prey individuals even if they do not get consumed by the predator. Here I review the role of basolateral amygdala neurons in the mediation of non-consumptive effects of predation. This brain region is critical for the generation and maintenance of fear response across many phylogenetic groups. The exposure to cues of predator presence activates neurons within the basolateral amygdala. Hormones secreted during stressful episodes cause long-lasting structural changes in basolateral amygdala neurons, causing facilitation of endocrine response during subsequent exposure to stressful episodes like later predator exposure. Some studies also suggest that BLA is involved in creating anticipatory change in defensive behavior in response to the expectation of change in the environment.